Complementary description of Panonychus caricae Hatzinikolis, 1984, with the resurrection of the genus Sasanychus Ehara, 1978 (Acari, Prostigmata, Tetranychidae) - Arabuli, Tea; Matsuda, Tomoko; Negm, Mohamed W.; Gotoh, Tetsuo (Zootaxa, 2020)
A complementary description of Panonychus caricae Hatzinikolis, 1984, is presented based on the morphology of adult female and male individuals collected from fig trees (Ficus sp., Moraceae) in Greece. Morphological differences between Panonychus caricae and two closely related species, Panonychus ulmi (Koch, 1836) and Panonychus hadzhibejliae (Reck, 1947), are discussed. Panonychus caricae can be separated from two other Panonychus species using the length of the female dorsal setae in combination with the ratio between the length of female dorsal opisthosomal setae f2 and h1, and the ratio between the length of dorsal setae sc1 and h1. A phylogenetic maximum likelihood tree was constructed based on the cytochrome c oxidase subunit I (COI) gene of mitochondrial DNA (mtDNA) from 10 species of the subgenus Panonychus s.str. (including the re-described species P. caricae) and the only two species of the subgenus Sasanychus. The phylogenetic tree indicates that these 12 species are clearly separated from each other. The two subgenera, Panonychus s.str. and Sasanychus, comprise strongly supported monophyletic clades with 98% bootstrap values. The convergence of molecular and morphological data (dorsal setae set on tubercles or not, number of tactile setae on tibiae I and II, and patterns of the dorsocentral striae) suggests that Sasanychus should not be classified under the genus Panonychus. Consequently, molecular and morphological evidence supports the resurrection of the genus Sasanychus, which contains two species, S. akitanus (Ehara) and S. pusillus Ehara & Gotoh, as distinct from Panonychus. A key to the world species of Panonychus and Sasanychus is also provided.